Relationships between event‐related potentials and behavioral and scholastic measures of reading ability: A large‐scale, cross‐sectional study. Issue 5 (30th July 2015) - Khalifian, Negin; Stites, Mallory C.; Laszlo, Sarah
Abstract: In the cognitive, computational, neuropsychological, and educational literatures, it is established that children approach text in unique ways, and that even adult readers can differ in the strategies they bring to reading. In the developmental event‐related potential (ERP) literature, however, children with differing degrees of reading ability are, the majority of the time, placed in monolithic groups such as 'normal' and 'dyslexic' (e.g. Araújo et al ., 2012) and analyzed only at the group level. This is likely done due to methodological concerns – such as low sample size or a lack of statistical power – that can make it difficult to perform analysis at the individual level. Here, we collected ERPs and behavior from > 100 children in grades pre‐K–7, as they read unconnected text silently to themselves. This large sample, combined with the statistical power of the Linear Mixed Effects Regression (LMER) technique, enables us to address individual differences in ERP component effects due to reading ability at an unprecedented level of detail. Results indicate that it is possible to predict reading‐related report card scores from ERP component amplitudes – especially that of the N250, a component pertaining to sublexical processing (including phonological decoding). Results also reveal relationships between behavioral measures of reading ability and ERP component effects that have previously been elusive, such as the relationship between vocabulary and N400 mean amplitude (cf. Henderson et al ., 2011). We conclude that it is possible to meaningfully examine reading‐related ERP effects at the single subject level in developing readers, and that this type of analysis can provide novel insights into both behavior and scholastic achievement. Abstract : This report presents the results of a very large (N > 100) developmental ERP study that aimed to link ERP component amplitudes with behavioral and scholastic measures of reading achievement. Results indicate a primacy of phonological ERP components for predicting scholastic reading success.